2021
DOI: 10.3390/rs13051033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Multi-Sensors Spectral and Spatial Resolutions for Tree Species Diversity Prediction

Abstract: Forests contribute significantly to terrestrial biodiversity conservation. Monitoring of tree species diversity is vital due to climate change factors. Remote sensing imagery is a means of data collection for predicting diversity of tree species. Since various sensors have different spectral and spatial resolutions, it is worth comparing them to ascertain which could influence the accuracy of prediction of tree species diversity. Hence, this study evaluated the influence of the spectral and spatial resolutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 84 publications
1
6
0
1
Order By: Relevance
“…Although our results showed a correlation between species diversity and the red and blue bands, this correlation was positive, similar to Conti et al [61]. The positive correlation between the diversity indices (S and H ′ ) and spectral reflectance of bands 6 and 2 of the PlanetScope data confirms their sensitivity to the nature and structure of the forest and the vegetation properties (Gyamfi-Ampadu) [62]. According to Kulawardhana.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although our results showed a correlation between species diversity and the red and blue bands, this correlation was positive, similar to Conti et al [61]. The positive correlation between the diversity indices (S and H ′ ) and spectral reflectance of bands 6 and 2 of the PlanetScope data confirms their sensitivity to the nature and structure of the forest and the vegetation properties (Gyamfi-Ampadu) [62]. According to Kulawardhana.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are consistent with those of Gyamfi-Ampadu. [62] and Imran et al [63] who demonstrated that the red part of the spectrum, that is, the red band, was best for estimating species diversity, hence their correlation with the species diversity (S and H ′ ). It must also be noted that the reserve lies in Ghana's tropical moist, semi-deciduous south-east forest zone and hence receives higher annual rainfall and a short dry season.…”
Section: Discussionmentioning
confidence: 99%
“…These presumptions are frequently challenging to prove (Dong et al, 2018;Cai et al, 2019). In the last decade, new satellites with higher spectral, spatial, and temporal resolution in combination with machine learning (ML) algorithms have given new insights into mapping TSC (Gyamfi-Ampadu et al, 2021, Waser et al, 2021.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed from the existing literature that there has been limited focus on the impact of bit depth on the information extraction process in remote-sensing images. In contrast, the influence of spatial [33,34] and spectral [35][36][37] resolution on remote-sensing data has been extensively studied in regards to classification accuracy and informationextraction capabilities. The results of cloud segmentation through remote sensing would be influenced by the bit depth of remote-sensing images [38].…”
Section: Introductionmentioning
confidence: 99%